2021
DOI: 10.30834/kjp.34.1.2021.262
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Problems among Medical Students during COVID-19 Lockdown: A Cross- Sectional Study

Abstract: Background: COVID-19, which originated in China, became a pandemic affecting more than 180 countries. By April 2020, India had announced lockdown in an attempt to control the spread of the virus. Lack of social interaction and apprehension about the studies had created emotional disturbances among medical students. Methods: The study was done in a medical college situated in Central Travancore, Kerala, between 2020 April 20 to May 31. Depression Anxiety Stress Scale (DASS) and Impact Event Scale-Revised (IES-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
1
1
Order By: Relevance
“…27 The prevalence of anxiety and depression in medical students during the pandemic was assessed in some countries and various parts of India and these studies demonstrated a high prevalence for both anxiety and. 18,20,22,24,32,33 The study conducted in the Institute of Medical Sciences, Banaras Hindu University, Varanasi in April 2020 showed prevalence of anxiety and depression among 9.8% and 7.3% of the participants which was relatively low compared to our study and other studies. 19 Our study was able to conclude that anxiety and depression was prevalent in the medical student fraternity.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…27 The prevalence of anxiety and depression in medical students during the pandemic was assessed in some countries and various parts of India and these studies demonstrated a high prevalence for both anxiety and. 18,20,22,24,32,33 The study conducted in the Institute of Medical Sciences, Banaras Hindu University, Varanasi in April 2020 showed prevalence of anxiety and depression among 9.8% and 7.3% of the participants which was relatively low compared to our study and other studies. 19 Our study was able to conclude that anxiety and depression was prevalent in the medical student fraternity.…”
Section: Discussioncontrasting
confidence: 81%
“…26 Multiple studies concluded that completion of their course, future studies, and employment were a major concern among medical students. 20,23,24 So, its pivotal to assess the mental health of the medical students their knowledge of mental illnesses during these testing times and hopefully support the findings of the previously conducted studies in order to raise awareness towards the mental health of medical students and the whole student body in general. The evidence thus generated can also be used to create supportive mental health care institutional structures for medical students.…”
supporting
confidence: 55%
See 1 more Smart Citation